An investigation of key predictors of performance of agricultural projects in Sub-Saharan Africa: A case of Uganda - Nkuruziza, Gideon; Kasekende, Francis; Omuudu Otengei, Samson; Mujabi, Shafic; Mpeera Ntayi, Joseph (International Journal of Social Economics, 2016)
The purpose of this paper is to examine the ways of improving performance of agricultural projects through stakeholder engagement and knowledge management in a Sub-Saharan context. Design/methodology/approach – Data were collected using a self-administered questionnaire from 342 agricultural projects in Mukono and Wakiso districts in Uganda. Descriptive statistics and inferential statistics were used in the analysis. Findings – The results reveal that stakeholder engagement and knowledge management are valuable intangible resources that significantly influence performance of agricultural projects. The findings, managerial and policy implications are fully discussed in this paper. Originality/value – The authors empirically show that a model that synchronizes stakeholder engagement, knowledge management and performance of agricultural projects is a requirement for promoting sustainable agricultural performance outcomes. This study makes a contribution by providing information that is relevant for filling the practical gap that exists in agricultural projects of Sub-Saharan Africa as well as contributing to the theoretical development of project management discipline.
Keywords: Uganda; Stakeholder engagement; Performance; Sub-Saharan Africa; Knowledge management; Agricultural projects